The sexual education of Edith Wharton - Erlich, Gloria C. (Berkeley : University of California Press, 1992)
Starting with the tensions in the early family constellation, Gloria C. Erlich traces Edith Wharton's erotic evolution--from her early repression of sexuality and her celibate marriage to her discovery of passion in a rapturous midlife love affair with the bisexual Morton Fullerton. Analyzing the novelist's life, letters, and fiction, Erlich reveals several interrelated identity systems--the filial, the sexual, and the creative--that evolved together over the.
Includes bibliographical references (pages 191-196) and index.
Print version record.
English.
JSTOR
Keywords: Wharton, Edith, -- 1862-1937 -- Psychology; Wharton, Edith, -- 1862-1937 -- Knowledge -- Psychology; Wharton, Edith, -- 1862-1937 -- Relations with men; Wharton, Edith, -- 1862-1937; Women and literature -- United States -- History -- 20th century; Psychological fiction, American -- History and criticism; Authors, American -- 20th century -- Psychology; Femininity in literature; Psychoanalysis and literature; Women in literature; Sex in literature; Femmes et littérature -- États-Unis -- Histoire -- 20e siècle.; Écrivains américains -- 20e siècle -- Psychologie; Féminité dans la littérature.; Psychanalyse et littérature.; Femmes dans la littérature.; Sexualité dans la littérature.; LITERARY CRITICISM -- American -- General; LITERARY CRITICISM / American / General; Authors, American -- Psychology; Femininity in literature; Relations with men; Psychoanalysis and literature; Psychological fiction, American; Psychology; Sex in literature; Women and literature; Women in literature; United States; Seksualiteit; 1900-1999; English fiction; United States; Criticism, interpretation, etc; History